PENDIDIKAN HAK KEKAYAAN INTELEKTUAL SEBAGAI PEMBEKALAN MENHADAPI PERGURUAN TINGGI - Radian Suparba; M. Zaid; Widodo, Widodo (Bajang Institute, 2026)
All copyrights and patents of higher education institutions, as described above, are the result of research efforts, whether by lecturers themselves or through collaborations between lecturers and students. Research is a mandatory activity for lecturers at higher education institutions, planned in advance and implemented in the form of publications or IPR. Students are also required to conduct research as their final assignments, a common perception of universities among most school students. However, it is important to consider that after graduating from high school, students are no longer